APOAV (T-1131>C) variant has no effect on mother's height in a large population study - Hubacek, Jaroslav A; Skodova, Zdena; Adamkova, Vera; Lanska, Vera; Bobkova, Dagmar; Poledne, Rudolf (Lipids in health and disease, 2004)
The important role of APOAV gene T-1131>C variant in determination of plasma triglyceride levels has been proved on many population studies. Recently, associations between C-1131 allele and higher mother's height as well as with longer fetal birth length were suggested. In 1,305 females, aged between 28 and 67 years and having at least one child, we have analyzed a putative association between T-1131>C APOAV variant (analyzed by PCR and restriction analysis) and body height. Mother's body height did not differ between T/T homozygotes (N = 1093, 162.5 +/- 6.5 cm) and C allele carriers (N = 212, 162.1 +/- 6.4 cm). Thus we have failed to confirm, that mothers with APOAV C-1131 allele are higher than T/T-1131 homozygotes.